Answer:
The correct option is C) x = y − 6.
Explanation:
Consider the provided equation.
![y = x + 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wqdrbnb6ld15wmgltueuzx9oqmt6m4dnxn.png)
We need to solve the provided equation for x.
Subtract 6 from both the sides.
![y-6 = x + 6-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/idigh5vxrobbebz1im2b02ig532pjgbifv.png)
![y-6 = x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xpsxbvay057txa8yzozp8ifmvuo8r1cji9.png)
![x=y-6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/30m43jfi56trlnm4iupuwoc146d3p6ctcd.png)
Thus, the value of the equation for x is
.
Hence, the correct option is C) x = y − 6.